Improvement of Thermoelectric Properties through Reduction of Thermal Conductivity by Nanoparticle Addition and Stoichiometric Change to Mg2Si. (10th August 2017) - Yorgason, William T.; Barnes, Arden N.; Roberts, Nick
ABSTRACT: Thermoelectric materials have been of interest for several decades due to their ability to recapture waste heat of various systems and convert it to useful electricity. One method used to improve the thermoelectric efficiency of a material is to reduce the lattice thermal conductivity ( k p ) while not affecting the other properties. In order to reduce the k p of the material, this paper introduces silicon (Si) nanoparticles (NPs) in Mg2 Si to manipulate phonon scattering and mean free path. A series of simulations is performed with the metal silicide thermoelectric material Mgx Six . The objective of this work is two-fold: 1) to determine the optimal Si nanoparticle (NP) concentration and 2) to determine the optimal Mgx Six stoichiometry for minimizing the k p of the system. It should be noted, however, that the assumed reduction in thermal conductivity is only a result of reduced phonon transport and that minimal impact is made on the transport of electrons. Interestingly, the uniform off-stoichiometry (49.55 atomic percent ( a/o ) Si) sample of Mgx Six resulted in a reduction of k p of 84.62 %, while the Si NP sample, with matching a/o Si, resulted in a reduction of k p of 78.82 %.